Modified Ishikawa iteration process for two nonexpansive semigroups in CAT(0) spacess - Eslamian M. (2014)
In this paper, we introduce modified Ishikawa iteration process for two nonexpansive semigroups in CAT(0) spaces. Then, we prove strong and Δ-convergence theorems for such iterative process in CAT(0) spaces. Moreover, we present Δ-convergence theorems of Ishikawa iteration process for a family of nonexpansive mappings in CAT(0) spaces. The results obtained in this paper extend and improve some recent known results.